2023
DOI: 10.1021/acs.biomac.2c01369
|View full text |Cite
|
Sign up to set email alerts
|

Photoreactive Mercury-Containing Metallosupramolecular Nanoparticles with Tailorable Properties That Promote Enhanced Cellular Uptake for Effective Cancer Chemotherapy

Abstract: A new potential route to enhance the efficiency of supramolecular polymers for cancer chemotherapy was successfully demonstrated by employing a photosensitive metallosupramolecular polymer (Hg-BU-PPG) containing an oligomeric poly(propylene glycol) backbone and highly sensitive pH-responsive uracil-mercury-uracil (U-Hg-U) bridges. This route holds great promise as a multifunctional bioactive nano-object for development of more efficient and safer cancer chemotherapy. Owing to the formation of uracil photodimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
0
6
0
1
Order By: Relevance
“…Metallosupramolecular coordination polymers through hydrogen bonding interaction from the nucleobase provide unique physical properties including pH sensitivity and tunable structural features due to the presence of hydrogen-bonded nucleobase moieties. For instance, uracil–mercury–uracil (U–Hg–U) and (Cy-Ag-Cy) linkages within supramolecular polymers exhibited extraordinarily blue fluorescence behavior due to extended conjugation of the U/C moieties providing stable sp 2 orbitals that overlap with the π-systems, which is promising for bioimaging. ,, These metallosupramolecular polymeric nanoclusters paved the way for the fabrication of imaging agents that can be effectively used for diagnosis purposes without the need for additional fluorescent probes.…”
Section: Biomedical Applications Of Nucleobase-decorated Supramolecul...mentioning
confidence: 99%
See 3 more Smart Citations
“…Metallosupramolecular coordination polymers through hydrogen bonding interaction from the nucleobase provide unique physical properties including pH sensitivity and tunable structural features due to the presence of hydrogen-bonded nucleobase moieties. For instance, uracil–mercury–uracil (U–Hg–U) and (Cy-Ag-Cy) linkages within supramolecular polymers exhibited extraordinarily blue fluorescence behavior due to extended conjugation of the U/C moieties providing stable sp 2 orbitals that overlap with the π-systems, which is promising for bioimaging. ,, These metallosupramolecular polymeric nanoclusters paved the way for the fabrication of imaging agents that can be effectively used for diagnosis purposes without the need for additional fluorescent probes.…”
Section: Biomedical Applications Of Nucleobase-decorated Supramolecul...mentioning
confidence: 99%
“…A further investigation carried out by the same group revealed that photoreactive mercury-containing metallosupramolecular polymer (U−Hg− U) undergo UV irradiated photo-cross-linking in aqueous solution and the resulting nanoparticle achieved rapid cellular internalization into solid tumors reiterating the prospect of selfassembled supramolecular polymers as a promising platform for efficient cancer chemotherapy. 113 4.2. Bioimaging.…”
Section: High Drug Loading Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past few decades, various nanoparticles (NPs) have been developed specifically for cancer treatment. 2,3 However, many early NPs failed to demonstrate satisfactory pharmaceutical outcomes clinically due to various limitations and obstacles. 4−9 These limitations include a short plasma half-life, inconsistent drug encapsulation efficiency (EE), erratic drug release, limited membrane permeability, systemic toxicity, and drug resistance.…”
Section: Introductionmentioning
confidence: 99%